Health Belief Model: Analysis of Maternal Perception on Completeness of Child Immunization Status in Manokwari, West Papua - Pihahey, Priscilla Jessica (Journal of Maternal and Child Health, 2025)
Background: Immunization can save millions of lives and is one of the most economical health interventions in the world. Parental perception is crucial in decision-making, but the mother’s characteristics, family, beliefs, culture, and environment influence perception. The Health Bilieu Model theory can show evidence that supports predictions about parents’ decisions to immunize their children. Subjects and Method: The design of this study is observational analysis with a case-control design. The research was conducted in 3 working areas of the Puskesmas in the Manokwari district, namely the Prafi SP IV Health Center, the Pasir Putih Health Center, and the Sanggeg Health Center. The research was conducted from July to August 2023. The target population is mothers who have children >9 months old. A total of 96 samples were selected using the fixed disease sampling technique. The incomplete immunization case group was 24, and the complete immunization control group was 72. The dependent variable is the completeness of immunization status, and the independent variable is the maternal perception of threats, benefits, seriousness, obstacles, and vulnerabilities. The data were analyzed by PATH analysis. Results: The completeness of basic immunization, as reviewed from the Health Belief Model during the Covid-19 Pandemic, was directly influenced by the perception of barriers to the completeness of immunization status (b= 0.99; 95% CI= -0.43 to 2.02; p= 0.060), the perception of benefits to the completeness of immunization status (b= 1.15; 95% CI= 0.11 to 2.19; p= 0.029) and the perception of threats to the completeness of immunization status (b= 1.36; 95% CI= 0.30 to 2.41; p= 0.012). Indirect influence through threat perception is: Vulnerability perception (b= 0.08; 95% CI= -0.87 to 1.04; p= 0.858) and Vulnerability perception (b= 0.25; 95% CI= -0.69 to 1.18; p= 0.606).   Conclusion: Maternal characteristics and maternal perception of obstacles, benefits, threats, seriousness, and vulnerability significantly affect the completeness of basic immunization for infants aged 0 months to 9 months.